The interaction evolution between thermally activated α precipitates and deformation-induced α’ martensite in a metastable β-Zr alloy - Tao Liu; Jiyan Ma; Zhongni Liao; Lin Lin; Ke Yang; Xinyue Lin; TaoTao Wang; YaPeng Li; Hui Zhang; TaoTao Ai (Journal of Materials Research and Technology, 2024)
In this study, the interaction evolution between the α precipitates that are thermally actived and deformation-induced α′ martensite in a metastable β-Zr alloy during tensile deformation was investigated. Following a two-step heat treatment, it results in the simultaneous precipitation of the thermally activated α phase in both within the β grain (αIN) and at the grain boundaries (αGB). The microstructure after deformation demonstrates that the α′ martensite induced by deformation initially nucleates and subsequently develops into elongated plates that are parallel with each other in the spaces between the αIN. As deformation continues, the α′ martensite grows rapidly in the length direction, firstly facing initial obstruction from αIN, but finally penetrating it and persisting to develop further. However, the growing α′ martensite encounters αGB, it is prevented completely from growing in length direction and instead grows quickly in width direction. Furthermore, α′ martensite plates further thicken and merge with each other, ultimately enveloping the complete β grain, including αIN, to construct an α′ martensite domain featuring an unusual shell-core arrangement. The shell layer is αGB and the core layer is α′ martensite surrounding αIN. Meanwhile, the secondary deformation product, namely {101‾1} twins, will form within α′ martensite domain in subsequent deformation process.